Democracy and innovation: from institutions to agency and leadership. Issue 3 (15th April 2016) - Helms, Ludger
Abstract : Democracies are, by definition, marked by a strong normative commitment to innovation and change, and all democratic regimes must seek to generate innovations both to keep their fundamental promise and to secure their own survival. In response to the latent crisis of representative democracy, recent political research has devoted eager attention to innovating democratic institutions, yet with conspicuously little regard for the likely effects of such reform proposals on the innovation-related performance and innovation capacity of democratic regimes. Indeed, some reform proposals, if implemented, would appear to reduce rather than increase the innovation capacity of representative democracies. Innovation-focused leadership may be able to fill that gap and provide what even the best institutions alone are unable to accomplish. In contrast to recent research on leadership and innovation in the public sector, which tends to centre on forms of collaborative leadership within networks, this article emphasizes the importance of individual leaders, and more specifically of political chief executives whose status and position in the governance process have been significantly enhanced by a combination of different factors. However, while leadership might be the key to democratic political innovation, innovative leadership and institutional engineering remain closely related to one another.